2018
DOI: 10.2337/db17-1238
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-129 and -335 Promote Diabetic Wound Healing by Inhibiting Sp1-Mediated MMP-9 Expression

Abstract: Diabetic wounds are recalcitrant to healing. However, the mechanism causing this dysfunction is not fully understood. High expression of matrix metalloproteinase-9 (MMP-9) is indicative of poor wound healing. In this study, we show that specificity protein-1 (Sp1), a regulator of MMP-9, binds directly to its promoter and enhances its expression. Additionally, we demonstrated that Sp1 is the direct target of two microRNAs (miRNAs), miR-129 and -335, which are significantly downregulated in diabetic skin tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(127 citation statements)
references
References 49 publications
4
123
0
Order By: Relevance
“…To further identify the underlying mechanism, a Western blot assay was conducted, and we found that like the SP1 protein, the MMP9 protein was also downregulated after siRNAs were transfected into T24 and UM-UC3 cells (Figure 4(c)). Previous studies showed that SP1, as a transcription factor, could specifically bind to the promoter site of MMP9 and enhance MMP9 expression [29][30][31]. So we conducted a ChIP assay in UM-UC3 cells.…”
Section: Knockdown Of Sp1 Inhibits Migration In Bca and Downregulatesmentioning
confidence: 99%
“…To further identify the underlying mechanism, a Western blot assay was conducted, and we found that like the SP1 protein, the MMP9 protein was also downregulated after siRNAs were transfected into T24 and UM-UC3 cells (Figure 4(c)). Previous studies showed that SP1, as a transcription factor, could specifically bind to the promoter site of MMP9 and enhance MMP9 expression [29][30][31]. So we conducted a ChIP assay in UM-UC3 cells.…”
Section: Knockdown Of Sp1 Inhibits Migration In Bca and Downregulatesmentioning
confidence: 99%
“…A large amount of inflammatory mediators, such as tumor necrosis factor (TNF)-a and interleukin (IL)-6, secreted by cells were released into the wound site and subsequently prevented the cell proliferation and migration required for diabetic wound healing [5]. Furthermore, over-activation of inflammation increased matrix metalloproteinase (MMP)-9 expression [6,7], which resulted in rapid degradation of native collagen, fibronectin, and elastin, thus delaying the diabetic wound-healing process [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have identified various miRNAs involved in cell differentiation and skin wound healing [16,17]. One of these important miRNAs is miR-203.…”
Section: Introductionmentioning
confidence: 99%